The relationships between Risk Factors and the changes of Histopathological of Tissue Colon Cancer in Iraq Patients - Sabreen S. Abd Alkreem Alsaqi (Zien Journals, 2023)
The transformation of an ordinary cell into a cancerous one could be a dynamic process which often involves the approval of oncogenes as well as deactivation of tumor suppressor properties (alterations). Most changes are emptied by cellular genome dauntlessness and repair components. In any case, many genetic changes give cells an advancement advantage and unused capacities, driving to their neoplastic alter. As other cancers, like melanoma, sarcoma, and lymphoma, could affect the colon, colon cancer, also known as colon carcinoma, affects the epithelium of colon. The uncontrolled proliferation regarding colorectal epithelial cells might be a hallmark of colorectal cancer (CRC). The multistep carcinogenesis hypothesis states that pigment cells go through a sequence of atomic alterations before they become totally dangerous cells. The inactivation related to the Adenomatous polyposis coli (APC) signaling pathway is the most frequent hereditary cause of activation. The pathology of damage includes oncogene changes, tumor suppressor qualities, and probably many signaling pathways, which put cancers at risk of metastasis. In advanced nations, CRC has a high disease-specific mortality rate and impacts over a million individuals annually. Worldwide, CRC ranks 3 rd in terms of the incidence in both women and men. Africa and Central and South Asia have experienced the biggest drops in CRC, whereas New Zealand, Australia, North America, and Europe have experienced highest change rates.
Keywords: colon cancer; Histopathological; Risk factors